(untitled) (Neo Scientific Peer Reviewed Journal, 2025)
The article discusses the issues of virtual infidelity as one of the factors leading to divorce and the opinions of scientists on this issue. Today, divorces are increasingly occurring due to virtual infidelity. Based on this, the article developed an author’s definition of the concept of virtual infidelity. Also, the controversial debate about the fact that virtual infidelity causes the breakdown of the family is discussed.